Getting Stuck in the Status Quo Ante: Evidence from the Egyptian Economy - Ömer Tuğsal Doruk; Francesco Pastore (Institute of Labor Economics (IZA), 2022)
In this study, for the first time, to our knowledge, we use the propensity score matching algorithm to estimate the probability to remain 'stuck in the status-quo ante' across generations in Egypt. We use repeated cross-sectional data relative to a 20-year period from 1998 to 2018 to build transition matrices of intergenerational occupational mobility. The findings of the econometric analysis hint at a low degree of occupational mobility, with children of fathers in the agricultural sector or holding a blue- or white-collar job remaining linked to the profession of their fathers in most cases and experiencing only rarely upward mobility from agricultural to blue- and white-collar jobs.
Keywords: C35; D64; J24; J62; L16; 330; intergenerational occupational mobility; status quo bias; propensity score matching; Egypt